1974
DOI: 10.1073/pnas.71.6.2549
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Viral Replication. Structure of Replication Complexes of Encephalomyocarditis Virus

Abstract: The structure of the purified replicative intermediate of encephalomyocarditis virus was determined by electron microscopy. Approximately 80% of the replicative intermediate complexes were characterized by a filament of double-stranded RNA of widely variable length, which had a "bush" of single-stranded RNA at one end. In many examples one or more additional singlestranded bushes were appended internally to the doublestranded RNA filament. These results support the view that before deproteinization, replicativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1975
1975
1986
1986

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Recent electron microscope studies have shown variability in the size of double-stranded segments in the RI of encephalomyocarditis virus (18). In our experiments, the proportion of RI in sucrose gradients that reacted with the antibodies increased as the sedimentation constant decreased toward 18S.…”
Section: Discussionsupporting
confidence: 54%
“…Recent electron microscope studies have shown variability in the size of double-stranded segments in the RI of encephalomyocarditis virus (18). In our experiments, the proportion of RI in sucrose gradients that reacted with the antibodies increased as the sedimentation constant decreased toward 18S.…”
Section: Discussionsupporting
confidence: 54%
“…Although the RNA backbone of RI molecules is believed to be ss in vivo, it assumes a ds-form upon extraction and isolation (35,10). RF is considered to comprise fully doublestranded (ds) RNA molecules consisting of one full-length genomic (plus strand) molecule and one full-length complementary (minus strand) molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that with the 'diffusion' method of Gordon (1973), who treats the surface of mica with aluminium chloride, and with the method of Highton & Whitfield (1974) no such 'thick and short' regions are found, is no argument against this hypothesis, since the supports used in their procedures bind nucleic acid molecules more weakly than does aluminium-beryllium. Also, the methods described earlier by Koller et al (1969), Dubochet et al (1971 and Thach & Thach (1973) cannot be taken into consideration in this connection, because of a possible unwinding interaction between the different ligands used and DNA is not excluded.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to obtain information with improved resolution, it is necessary to spread the nucleic acid strands without carrier protein and to adsorb the molecules to a smooth ('low noise') support film. Several protein-free nucleic acid preparation techniques have been described (Nanninga et al, 1972;Thach & Thach, 1973;Highton & Whitfield, 1974; for review Koller et al, 1971). All these techniques, however, use carbon as supports.…”
Section: Introductionmentioning
confidence: 99%